Fixed-point sensitivity maps for image reconstruction in tomography - Amirulah, Rahman (Penerbit UTM Press, 2015)
This study proposes new fixed-point sensitivity maps for image reconstruction in optical tomography systems by using a linear back projection (LBP) algorithm. The projection selected is based on fan beam orientation with 16 pairs of transmitters and receivers. Many optical tomography systems previously published, focused on microcontroller implementations, which have limited processing speed for real time systems to be used in critical applications such as underwater gas transmission pipeline. To gain benefits from parallel processing in digital hardware implementations such as using FPGA or ASIC, slight modification must be done in the reconstructed images mechanism. The normalized sensitivity maps for image reconstruction are recreated without using floating numbers to optimize the digital design implementations. By multiplying the sensitivity maps matrix with 128, the new sensitivity maps matrices are developed and rounding processes are performed to eliminate floating numbers. The error was determined using Normalized Mean Square Error (NMSE) and the results show that the new fixed-point sensitivity maps produced comparable image reconstruction quality for optical tomography systems with NMSE values of 1.88 × 10-7 and 0.02 for phantoms (a) and (b) respectively